Cellular morphology and markers of cartilage and bone in the marine teleost Sparus auratus - Estêvão, M. Dulce (2014)
Modifications have been characterised in terms of cellular organisation and the extracellular matrix (ECM) during bone ontogeny in the sea bream (Sparus auratus). During endochondral development, the agglomeration of matrix-secreting cells gives rise to chondrones; these chondrones frequently contain proliferating-cell-nuclearantigen-positive cells, which subsequently become large collagen-II-positive cells with the characteristics of chondrocytes. Moreover, the matrix:cell ratio within the perichondrium increases, accompanied by a modification in ECM composition. Mineralisation of cartilage ECM is marked by a rapid fall in cell number, the switching off of collagen II transcription and the switching on of collagen X transcription, followed by collagen I transcription and bone mineralisation. The formation of dermal structures initiated upon the condensation of mesenchyme cells defines the future location of the dermal bone. Subsequent cellular differentiation gives rise to cells on the bone surface; these cells are positive for collagen I and osteonectin transcripts. The fish skeleton, with the exception of vertebrae, tends to comprise flattened bones that are covered by a monolayer of cells, the periosteum. A third type of tissue, present in gills, consists of chondrocyte-like cells embedded in a mineralised matrix resembling chondroid bone in mammals. The results suggest that the cellular organisation and ontogeny of endochondral and dermal bone in the sea bream are similar to those described in other vertebrates.